2013
DOI: 10.1007/s12552-013-9107-9
|View full text |Cite
|
Sign up to set email alerts
|

The What, the Why, and the How: A Review of Racial Microaggressions Research in Psychology

Abstract: Since the publication of Sue et al. (Am Psychol 62:271–286, 2007a, b) seminal article, there has been an enormous scholarly interest in psychology on this construct of racial microaggressions—subtle everyday experiences of racism. In this paper, we provide a review of racial microaggressions research literature in psychology since 2007, following the publication of the first comprehensive taxonomy of racial microaggressions, which provided a conceptual framework and directions for research related to racial mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
264
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(276 citation statements)
references
References 73 publications
(112 reference statements)
8
264
0
4
Order By: Relevance
“…Replicating previous research (see Wong et al, 2013, for a review) every Person of Color in our sample reported experiencing at least one racial microaggression over the previous six months.…”
Section: Racial Group Differences In Racial Microaggressionssupporting
confidence: 78%
See 3 more Smart Citations
“…Replicating previous research (see Wong et al, 2013, for a review) every Person of Color in our sample reported experiencing at least one racial microaggression over the previous six months.…”
Section: Racial Group Differences In Racial Microaggressionssupporting
confidence: 78%
“…More generally, the cumulative experience of racial microaggressions is related to reduced positive affect, and increased depressive and somatic symptoms (Donovan et al, 2012;Huyng, 2012;Nadal, Griffin, Wong, Hamit, & Rasmus, 2014). Thus, like more blatant forms of discrimination (see Pascoe & Smart Richman, 2009, for a review), experiencing racial microaggressions can be detrimental to one's mental and physical health both immediately within the same 24-hour period and cumulatively over time (see Wong et al, 2013, for a review).…”
Section: Racial Microaggressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although discourses of inclusion may be drawn on to promote the image of formerly White schools as zones of equality and respect for diversity, exclusion and marginalisation of Black children continue (Sayed & Soudien, 2003), but may be difficult to address and think about because the language of inclusion is prominently used. Discrimination and exclusion are difficult to name and address in contexts where there is a dominant discourse of equality, as the international research on what are termed ‘microaggressions’ has shown (Sue, 2013; Wong, Derthick, David, Saw, & Okazaki, 2014). SA is not unique in having moved beyond a situation in which overt racism is no longer tolerated but in which, despite official non-racial and an-tiracist policies, subtle but keenly experienced practices of exclusion persist (Allen, Scott, & Lewis, 2013; Conradie & Brokensha, 2014).…”
Section: Integration or Exclusion In South African Education?mentioning
confidence: 99%